LONG-CIRCULATING LIPOSOMES AS A PROMISING STRATEGY FOR THE TRANSPORT AND BIOAVAILABILITY OF DRUGS IN CANCER TREATMENT - Freitas, Camila Fabiano de; Batistela, Vagner Roberto; Caetano, Wilker; Hioka, Noboru (Uningá Review, 2020)
In recent years, nanotechnology has been a strong ally to Medicinal Chemistry. Liposomes stand out, being cell membrane models and excellent biocompatible drug delivery systems. However, liposomes have limitations due to their low stability in solutions and rapid elimination from the blood stream. These factors prevent the accumulation of these structures in tumor tissues, as well as the effects of permeability and retention (EPR effect). Given this scenario, several strategies have been developed aiming to increase the stability and the circulation of liposome in the blood stream. Recent research has shown that surface-modified liposomes with polyethylene glycol (PEG), triblock ABA-like copolymers or site-specific ligands are able to overcome these issues. With that in mind, this article brings a review of the main scientific contributions in the development, optimization and improvement of liposomes as long circulation systems aiming at new strategies for drug formulation in cancer treatment.